ANALISIS NILAI TAMBAH GULA KELAPA INDUSTRI RUMAH TANGGA DI DESA GUNTURHARJO KECAMATAN PARANGGUPITO KABUPATEN WONOGIRI - Pambowo, Anjas Nur; Dewati, Rosita; Harinta, Yos Wahyu (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2024)
Coconut sap is the raw material used for making coconut sugar in Gunturharjo Village, Paranggupito District, Wonogiri Regency. The research objective is to determine the value added of coconut sugar. The basic research method uses a qualitative design with a quantitative approach. Purposive location taking. Respondents are owners of the coconut sugar industry, numbering 5 household industries in Gunturharjo village. The analysis method uses the hayami method. The research results show that IRT coconut sugar provides value added for producers. For every processing of 1 kg of sap, an average of 0.19 kg of sugar is produced. This sugar industry provides added value of IDR 2,612 per kg or 56.41% so it can be classified as high because the value added ratio is > 40%. The coconut sugar industry barbarslot is still labor intensive, based on the hayami method, it shows that labor income is greater than the profits of business owners who are able to absorb labor and use simple equipment with limited capital. Keywords: Coconut,Sugar, Hayami.